Does Social protection improve female-headed households' food security in Ebinat district, Ethiopia - Belainew Belete; Tadele Bayu Genet (Cogent Economics & Finance, 2023)
Though social protection in sub-Saharan Africa is intensive to alleviate food insecurity of the vulnerable group such as women, its impact on the food security status of female-headed rural households has not been well documented. Accordingly, the present study aims to evaluate the effect of the Productive Safety Net Program (PSNP) on the food security of female-headed farm households. The study employs the Propensity Score Matching (PSM) method to identify the comparable beneficiary and non-beneficiary sample households. The study finding indicates that PSNP improves the food security status of female-headed farm households. Moreover, the study suggested that the food security status of the beneficiary household is better than the non-beneficiary household even after controlling the potential heterogeneity. Based on the findings of the present study, we recommend that PSNPs should focus on building a sustainable income-generating livelihood system.
Keywords: H55; H84; I39; 330; Food security; impact analysis; Productive Safety Net Program; propensity score matching